Adsorption cooling system employing activated carbon/R32 adsorption pair - Askalany, A.A. (EDP Sciences, 2014)
This paper reports the performance of an adsorption cooling system employing activated carbon powder (Maxsorb III)/R32 adsorption pair. The system has been modeled and simulated numerically and the effect of changing the operating conditions has been studied. The system has been simulated to driven by a low-grade heat source temperature below 90Â°C and effectively employs solar heat and/or waste sources to drive the system. Â© 2014 Owned by the authors, published by EDP Sciences.